Analisis Model Pengelolaan Zakat, Infaq dan Shadaqah (ZIS) di Mesjid Al Istiqomah Kabupaten Bandung Barat - Amrullah Hayatudin; Arif Rijal Anshori (Jurnal Ilmiah Ekonomi Islam, 2021)
This research was conducted as an effort to find the right model in the management of Zakat, Infaq, and Sadaqah (ZIS) at the Al Istiqomah Mosque, Taman Bunga Cilame districts of West Bandung. With the hope of an appropriate model in the management of Zakat, Infaq, and Shadaqah (ZIS) funds. The purpose of Zakat, Infaq, and Shadaqah (ZIS) as a means of worship and social means, namely as a means to alleviate poverty and prosper the people can be achieved. The method used by researchers is qualitative, the data collection technique is observation (observation), interview (interview), and documentation, in analyzing the data the researcher uses qualitative data analysis is inductive. In managing ZIS funds, three things must be considered by DKM administrators, namely: Excellent service for muzakki and mustahik, funds (ZIS) must be utilized properly, transparently, creatively, and innovatively. With the management model as follows: Providing additional capital to mustahik by using aqad Mudharabah or Musyarakah; Assistance with the Participatory Action Research (PAR) approach to mustahik.